2015
DOI: 10.2147/ndt.s94147
|View full text |Cite
|
Sign up to set email alerts
|

Increased mean platelet volume in patients with panic disorder

Abstract: ObjectiveThe relationship between platelet activation and psychiatric disorders has been shown in previous work. Mean platelet volume (MPV) is a measure of platelet size and a good indicator of platelet activity, which increases in cardiovascular diseases (CVDs). It is known that anxiety is a considerable factor in the etiology of mortality in CVDs. The aim of the present study was to investigate any probable difference in the MPV of patients with panic disorder (PD).MethodsSixty-one drug-free patients, aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 44 publications
1
40
2
1
Order By: Relevance
“…Results of the studies about MPV values in panic disorder patients were contradictory. Some reported that MPV values were higher in panic disorder patients [15,16] whereas others reported otherwise [14,17]. Increased MPV was attributed to activation of platelets via α-2 receptors and decreased MPV was attributed to 5-HT transporter rate and its metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the studies about MPV values in panic disorder patients were contradictory. Some reported that MPV values were higher in panic disorder patients [15,16] whereas others reported otherwise [14,17]. Increased MPV was attributed to activation of platelets via α-2 receptors and decreased MPV was attributed to 5-HT transporter rate and its metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Increased MPV levels are thought to be closely related to cardiovascular disorders [13]. MPV values were studied in also schizophrenia, bipolar disorder and panic disorder with contradictory and inconclusive results [14][15][16][17][18]. We could not find any study evaluating the MPV levels in GAD patients in the literature.…”
Section: Introductionmentioning
confidence: 97%
“…In patients with PD, platelet aggregation has been shown to be elevated via changes in nitrous oxide and homocysteine levels [80]. Finally, patients with PD have larger mean platelet volume, a marker of increased platelet reactivity [81]. …”
Section: Mechanisms Mediating the Relationships Between Anxiety Disormentioning
confidence: 99%
“…Besides, high MPV levels were also observed among patients who got depression or panic disorder (Buriachkovskaia et al, 2006; Kokacya et al, 2015). It has been established that MPV was associated with higher platelet reactivity (Bath & Butterworth, 1996; van der Loo & Martin, 1999; Yetkin, 2008), which is involved in the pathophysiological mechanisms of depression (Musselman et al, 1996; Nemeroff & Musselman, 2000).…”
Section: Introductionmentioning
confidence: 99%